Cryogenic machining of AISI p20 steel under liquid nitrogen cooling. (2021) - Ravi, S.; Gurusamy, P.
Abstract: Cryogenic Lubricants are fluids used for cutting which have significance and they are environmentally friendly; they are easily recyclable and they won't generate any hazardous by-products. The LN2 in −196 0 C is the very common lubricant in cryogenic metal removing operations. In the current work metal removing operation of AISI P20 hardened steel were carried out by a milling action using a coated tool made of carbide with cryogenic, flood cooling and dry conditions. Experiments were taken at a speed of cutting at 75, 100 as well as 125 m/min, the rate of the feed, and the in-depth of the cut which was kept constant in 0.2 mm /tooth as well as 0.5 mm perfectly. The tear and wear of the tool and surface roughness were measured. The data acquired from tests have revealed that cryogenic metal removing operations have yielded greater life of the tools compared to existing flood metal removing operation.